»Their dogs are of an alert and intelligent breed« An Ethnocynology of Tyvan Pastoralists in Inner Asia - Svanberg, Ingvar; Soyan Peemot , Victoria (Ethnobiology Letters, 2022)
This study presents a brief inquiry into the human-canine relationship among the Tyvan pastoralists in the Altai-Sayan Mountainous region of Inner Asia. Their co-evolution is intimately bound together, and the inter-species relationship includes several aspects and roles. The authors investigate especially the dogs’ responsibilities in taiga and steppe habitats and how the language reveals these responsibilities by focusing on distinctions between hunting dogs (aŋčï ït) and camp guarding dogs (kodančï ït). Both names point at the main tasks—hunting and guarding the seasonal campsite territory. The third category is named xava dogs; the name traces its origin to Chinese languages. Similarly, the story of a small-sized xava dog sheds a light on the Altai-Sayan Mountain region’s historical and religious connections with China.